Horns - Hill, Joe (William Morrow, 2010)
After his childhood sweetheart is brutally killed and suspicion falls on him, Ig Parrish goes on a drinking binge and wakes up with horns on his head, hate in his heart, and an incredible new power which he uses in the name of vengeance.